Analisis Kandungan Rodamin B dan Metanil Yellow Minuman di SD Lubuklinggau - Mareta Widiya; Reny Dwi Riastuti; Siti Wahyu Widiana (Journal of Indah Science and Clinic, 2021)
Food additives are substances that are mixed to improve the quality of food without nutrition, for example food and beverage coloring. rhodamine B and methanyl yellow, which were the focus to identify their presence in beverages at Elementary Schools (SD), Lubuklinggau Selatan II District. Descriptive research and accidental sampling, samples were tested directly by Test Kit of rhodamine B and methanyl yellow. The results showed that 3 of the 15 samples tested by the Rodamine B Test Kit were positive with an indication of a change in color to purplish red, and of the 13 samples tested by the methanyl yellow Test Kit, the color was the same as the initial color of the drink, there was no methanyl yellow content in the drink at SD Lubuklinggau Selatan II sub-district.